Phytochemical studies on Stemona plants: Isolation of stemofoline alkaloids - Sastraruji T. (2014)
Six new stemofoline alkaloids, (2′A)-hydroxystemofoline (5), (3′R)-stemofolenol (6), (3′S)-stemofolenol (7), 1′,2′- didehydrostemofoline-AT-oxide (8), the first C19 stemofoline alkaloid, methylstemofoline (9), and the first glycosidated Stemona alkaloid, stemofolinoside (10), and three known alkaloids, (2′S)-hydroxystemofoline (2), (HZ)-1′,2′-didehydrostemofoline (3), and (11E)-1′, 2′-didehydrostemofoline (4), have been isolated from a root extract of an unidentified Stemona species. The structure and relative configuration of these new alkaloids have been determined by spectral data interpretation and from semisynthetic studies. © 2005 American Chemical Society and American Society of Pharmacognosy.